Optimization of hydrogen production over TiO2 supported copper and nickel oxides: effect of photoelectrochemical features - Bashiri, R. (2019)
Low-cost solar hydrogen production through water splitting using photo-electrochemical (PEC) cell offers a clean and renewable source of energy. However, its low performance remains a primary concern. Solar hydrogen production of TiO2 supported copper and nickel oxides photoanod (CuâNi/TiO2) was significantly influenced by photoanode fabrication and reaction parameters. To maintain the optimum operating conditions of PEC cell for practical application, we systematically investigated the effect of sintering temperature, photoanode thickness, electrolyte concentration, and applied voltage on hydrogen production over 5Â mol CuâNi/TiO2 and PEC characteristics, including charge carrier transfer resistance, photocurrent density, and flat band potential. Findings reveal that the optimized sintering temperature for hydrogen production was 400Â Â°C due to low charge transfer resistance and more excited electrons at the electrode/electrolyte interface. The photocatalyst with the four layers of printed 5Â mol CuâNi/TiO2 (thickness ~ 24.8Â Âµm) improved the photocatalytic performance, highlighting the importance of the number of excited electrons and the surface area of the photocatalyst. Furthermore, applied voltage exerted the most significant effect on hydrogen production up to 24.9Â mL at the optimum level of 3.4Â V by minimizing the recombination rate of electronâhole pairs. The stability of the photoanode was tested under the optimum conditions for 4 days and the maximum accumulative hydrogen of 443.4Â mL was produced over this highly stable photoanode. Graphical abstract: Figure not available: see fulltext.. Â© 2018, Springer Nature B.V.